A Differential Diagnostic Tool for Identifying the Causes of Clover Decline - Beatrice Francisco Menezes; Annika Kühnl; Kristin Steinfurth; Ulrike Hakl; Irene Jacob; Jürgen Müller; Christel Baum; Christine Struck (Agronomy, 2025)
Forage legumes often show poor growth, the cause of which is not always immediately apparent to the farmer. The aim of the present study was the development of a diagnostic tool to identify possible causes for unexplained forage legume decline. A modified diagnostic test was carried out under a controlled environment using red clover (Trifolium pratense L.) as a test plant. Soil samples from three organic farms in Germany showing decline in productivity of forage legumes were tested using (i) an untreated control, (ii) application of a nutrient solution to investigate nutrient deficiencies, (iii) amendment with activated charcoal to immobilize toxic compounds, and (iv) heat sterilization to eliminate detrimental organisms. In addition, plant and soil samples from the three study sites were analyzed for pathogens and nutrient levels in the laboratory. At all the sites, plants growing in the sterilized soil showed an improvement in growth, indicating the presence of pathogens in the soil as the main cause for red clover decline. Hints at nutrient deficiency and a minor effect of phytotoxic compounds were found in addition to detrimental organisms at one studied site, indicating an interaction of abiotic and biotic factors as the cause of clover decline. The fertilization with a nutrient solution led to stunted growth at one site, which could be associated with a negative effect of nitrogen application on red clover and nutrient imbalances. The results of the bioassay were corroborated by the plant screening for pathogens and nutrient levels analyses. The diagnostic test proved to be a reliable tool for identifying possible causes of red clover decline, such as harmful organisms or, to a lesser extent, nutrient deficiencies.